A rare and independent association of Right Atrial Myxoma with Immune Thrombocytopenic Purpura - R., Karthik Raman; Palanisamy, Vijay Anand; Ravikumar, Mithun Sundararaja; Moses, Jeswin; Pandian, Sivakumar; Sethuratnam, Rajan (International Journal of Research in Medical Sciences, 2019)
Primary tumours of the heart are rare and the most common benign ones are myxomas. The clinical features are varied and include a myriad of presenting symptoms like embolic, constitutional, cardiac and also symptoms due to obstruction. Right atrial myxomas are very rarely seen when compared with left atrium. Such myxomas independently co existing with Immune Thrombocytopenic Purpura (ITP) is even rarer and we now present one such case in with right atrial myxoma was associated with ITP and was managed surgically. This case emphasises the fact that ITP can co-exist with myxoma and should be borne in mind when treating such patients surgically.